Pimps Up, Hoes Down?: The Amazing Misadventures of Blackface Masculinity (AmeriQuests, 2008)
This essay argues that the current framing of black masculinity within expose-style discussions have continually mired a needed conversation about the future of black masculinity within a discourse of “blackface masculinity.” Here, a literal minstrel show is enacted where the most canned, marketable, and enticing expressions of black masculine deviance in popular culture stand in for a more pointed conversation about the pervasiveness of an American brand of misogyny and homophobia. In the end, this blackface show is an American production that purposefully racializes dangerous expressions of masculinity as inherently “black,” limits black women to a vision of gender defined by social/sexual subservience to all men, and renders invisible current anxieties around gender relations that could help explain the attractive lure of his “blackface masculinity” for men across the color line.